2017
DOI: 10.1177/0743558417719188
|View full text |Cite
|
Sign up to set email alerts
|

Repression in Residential Youth Care: A Qualitative Study Examining the Experiences of Adolescents in Open, Secure and Forensic Institutions

Abstract: Repression in residential youth care institutions can manifest itself openly in coercive measures or may be concealed in staff behavior that is endemic to residential youth care, such as soft power and strict behavioral control (i.e., structure), which threatens rehabilitative goals and might even violate children’s rights. To increase awareness of particularly the more hidden aspects of repression, this qualitative study follows the framework method to examine processes that cause adolescents to experience re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 44 publications
4
31
0
Order By: Relevance
“…This resonates with findings on ‘procedural justice’ in other studies [35] and refers to aspects such as being fully informed of one’s own trajectory and prospects, as well as being listened to and having a say in decisions. This is also compatible with a recent study on adolescents’ experiences of repression in residential youth care, which decrease if their autonomy is respected and treatment is perceived as more personally meaningful [36].…”
Section: Discussionsupporting
confidence: 89%
“…This resonates with findings on ‘procedural justice’ in other studies [35] and refers to aspects such as being fully informed of one’s own trajectory and prospects, as well as being listened to and having a say in decisions. This is also compatible with a recent study on adolescents’ experiences of repression in residential youth care, which decrease if their autonomy is respected and treatment is perceived as more personally meaningful [36].…”
Section: Discussionsupporting
confidence: 89%
“…Academic literature in the field of (forensic) mental health discusses at length coercive measures such as restraint, seclusion and forced medication (Hui et al, 2013); the ethical issues of hospitalizing residents in psychiatric institutions (Adshead, 2000;Jones & Fowles, 1984;Völlm et al, 2016); resident satisfaction with forensic care (Bressington et al, 2011;MacInnes et al, 2010); human rights in psychiatric care (Penny & Exworthy, 2015) and institutionalization (Chow & Priebe, 2013) but no research has yet addressed the explicit question of how residents experience the restrictiveness of forensic care. 'Repression' in Dutch Youth Offender Institutes (YOIs) has however been explored (de Valk et al, 2016;de Valk et al, 2017). The authors define repression in YOIs as interactions between youth, staff and the institution that intentionally harms or unlawfully or arbitrarily deprives youth of their autonomy or liberty.…”
Section: 'Least Restrictive' Philosophymentioning
confidence: 99%
“…A review of the literature (De Valk et al 2015 and interviews with youth (De Valk et al 2017) showed that youth may experience different dimensions of institutional repression in residential youth care institutions. First, youth may experience that staff members abuse the power they possess.…”
Section: Conceptualizing Institutional Repressionmentioning
confidence: 99%
“…Power differences between staff and youth are an inevitable element of residential youth care, which staff can use to make and apply rules, to provide structure, to impose sanctions, and to use coercive measures (Goffman 1961). In general, youth seem to accept the exercise of power if they view it as necessary, and many adolescents think they benefit from strict rules or that it would be chaotic if there were no structure (De Valk et al 2017). However, youth experience repression when staff members use their power arbitrarily or excessively, for example, when rules are suddenly changed or made up, or when staff members use coercive measures when there is no crisis situation.…”
Section: Conceptualizing Institutional Repressionmentioning
confidence: 99%
See 1 more Smart Citation